The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41598-023-42362-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of proton therapy on the DNA damage induction and repair in hematopoietic stem and progenitor cells

Simon Sioen,
Oniecha Vanhove,
Barbara Vanderstraeten
et al.

Abstract: Proton therapy is of great interest to pediatric cancer patients because of its optimal depth dose distribution. In view of healthy tissue damage and the increased risk of secondary cancers, we investigated DNA damage induction and repair of radiosensitive hematopoietic stem and progenitor cells (HSPCs) exposed to therapeutic proton and photon irradiation due to their role in radiation-induced leukemia. Human CD34+ HSPCs were exposed to 6 MV X-rays, mid- and distal spread-out Bragg peak (SOBP) protons at doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the normal tissue response may vary depending on the complexity of DNA damage induced by different radiation modalities, as evidenced in the context of proton therapy compared to conventional photon-based radiotherapy for cancer treatment 10 . Indeed, recent studies have revealed that proton irradiation can elicit distinct DNA damage responses and activate specific pathways [11][12][13] , leading to more effective killing of cancer cells 11,14 . However, to date, the understanding of the molecular effects of proton versus photon irradiation on normal tissue is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the normal tissue response may vary depending on the complexity of DNA damage induced by different radiation modalities, as evidenced in the context of proton therapy compared to conventional photon-based radiotherapy for cancer treatment 10 . Indeed, recent studies have revealed that proton irradiation can elicit distinct DNA damage responses and activate specific pathways [11][12][13] , leading to more effective killing of cancer cells 11,14 . However, to date, the understanding of the molecular effects of proton versus photon irradiation on normal tissue is still limited.…”
Section: Introductionmentioning
confidence: 99%